CTIM-32. IMMUNE CHECKPOINT INHIBITOR NIVOLUMAB IN PEOPLE WITH RECURRENT SELECT RARE CNS CANCERS: RESULTS OF INTERIM ANALYSIS IN A HEAVILY PRETREATED COHORT. (12th November 2021) - Penas-Prado, Marta; Yuan, Ying; Wall, Kathleen; Vera, Elizabeth; Ikiddeh-Barnes, Ukeme; Blackburn, Katie; Chambers, Claudia; Ratnam, Nivi; Frederico, Stephen; Acquaye, Alvina; Aldape, Kenneth; Briceno, Nicole; et al.
Abstract: INTRODUCTION: Standard and experimental therapies for patients with rare CNS tumors are scarce. Nivolumab (PD-1 inhibitor) is approved for several non-CNS cancers. This ongoing Phase II trial (NCT03173950) will determine the efficacy of nivolumab in adults with recurrence/progression of one of 11 selected rare primary CNS tumors. Efficacy is measured by Disease Control Rate (DCR; confirmed CR/PR or durable SD for ≥ 6 months) in 2 cohorts: heavily and non-heavily pretreated patients (heavily pretreated: ≥ 3 prior therapies; non-heavily pretreated: ≤ 2). We report efficacy and safety results of a preplanned interim analysis in the heavily pretreated cohort. METHODS: Eligibility includes recurrence/progression of an eligible tumor; age ≥ 18 years; tumor tissue available for histopathology, molecular and immune profiling; KPS ≥ 70; and no steroids at study entry. A total of 150 evaluable patients will be enrolled (75 to each cohort). Prior therapies include radiation and/or standard or investigational drugs. Nivolumab treatment is 240 mg IV every 2 weeks (4 doses); then 480 mg every 4 weeks (14 additional doses). Interim analysis was planned when sample size reached 32 in each cohort. RESULTS: As of March 10, 2021, DCR exceeded the minimum required for interim analysis in the heavily pretreated cohort. Among 30 patients, 4 achieved SD > 6 months (medulloblastoma, anaplastic ependymoma, myxopapillary ependymoma, metastatic atypical meningioma). Safety profile (related AEs): grade 3 = 7; grade 4 = 1. Most frequent grade 3-5 AEs regardless of attribution: tumor progression (6); anemia, hydrocephalus, lymphopenia (3 each); cerebral edema, headache (2 each). CONCLUSION: DCR exceeded the "go" boundary (i.e., > 2) in the heavily pretreated cohort. Nivolumab showed safety profile consistent with other studies. This cohort will continue to stage 2 and complete total accrual of 75 patients. The trial is currently being expanded to 10 additional sites across the BTTC/NCI-CONNECT consortium.